A Meandered Inductive Loop Based RFID Tag Antenna for Luggage Tracking - Singh A.K. (My University, 2025)
In this paper, a planar tag antenna for UHF band RFID composed of a spiral ending meandered line with meandered inductive loop is presented. The presented novel compact spiral ended meandered tag having double sided meandered inductive loop microstrip dipoles scales down the extent of tag antenna and provides an upgraded conjugate impedance matching between tag antenna and semiconductor ASIC. This tag antenna operates at 866 MHz. Here, a compact UHF tag having volume of 60 × 16 × 1.6 mm3 (0.173λ× 0.046λ× 0.0046λ) is testified. This antenna produces impressive reflection coefficient and is able to access detection territory of 12.6 m. The proposed RFID antenna layout is simulated in favor of reader having 4 W EIRP. © 2023, Electromagnetics Academy. All rights reserved.